Synthesis of ultrathin PEDOT on carbon nanotubes and shear thinning xanthan Gum-H2SO4 gel electrolyte for supercapacitors - Soni, Roby; Bhange, Siddheshwar N.; Athira, E.; Chetry, Rashmi; Kurungot, Sreekumar (ChemElectroChem, 2019)
Resistance of the electrode material play a vital role for applications in supercapacitors, where lowering the resistance leads to improved performance. Poly(3,4-ethylene dioxythiophene) (PEDOT) possesses high theoretical conductivity; however, the high density of grain boundaries, low accessible surface area, and low rate capability have been pervasive issues affecting the PEDOT-based supercapacitors. To this end, a hydrothermal method is proposed in this work where oxygen functional groups incorporated on the surface of carbon nanotubes (CNTs) are utilized to polymerize 3,4-ethylenedioxythiophene (EDOT). PEDOT forms an ultrathin, well-aligned coating on the surface of CNTs. This arrangement minimizes the number of grain boundaries and increases the electrochemically active surface area. Additionally, a shear-thinning Xanthan gum-H2SO4 gel electrolyte is introduced to overcome the low impregnation of the conventional polyvinyl-based electrolyte due to the hydrophobicity of the CNT-PEDOT composite. A supercapacitor based on this material showed a very low Equivalent Series Resistance (ESR) of 0.31 which leads to a high power density of 74 W cm(-3).
Keywords: gel electrolyte; PEDOT; shear thinning; supercapacitor; xanthan gum